RISK-TAKING PROPENSITY AND FEAR OF PUNISHMENT AS PREDICTORS OF TRAFFIC RULES VIOLATION AMONG DRIVERS IN OYO STATE, NIGERIA - Aderibigbe, Sunday Y.; Olapegba, Peter O.; Abiahu, Keyna C.; Uye, Emmanuel E. (African Journal of Social and Behavioural Sciences, 2022)
Predictors of traffic rules violation among 240 drivers in Akinyele and Ibadan North Local Government Areas in Oyo State, Nigeria were investigated using accidental sampling technique. The variables investigated were risk-taking propensity, fear of punishment, traffic rules violation, gender, levels of education, and years of driving experience. Cross-sectional design was used for data collection while multiple regressions analysis, analysis of variance and t-test for independent samples were used for data analyses. The results indicated that risk-taking propensity and fear of punishment jointly predicted traffic rules violation among drivers. Also, levels of education and years of driving experience significantly influenced traffic rules violation among drivers. The implication of this study is that since drivers are not afraid of violation of traffic rules, the alternative explanation that many drivers feel that they can always buy their ways out when it comes to traffic rules violation should be investigated.